Group Exhibition-Soul , Sarajevo Historical Museum, Sarajevo Winter Festival - Antoniou, Klitsa (My University, 2026)
Soul , Sarajevo Historical Museum, Sarajevo Winter Festival, Bosnia Herzegovina. Curated by Ibrahim Spahich.